2004
DOI: 10.1017/s1479050503001066
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular composition of unsaturated Pseudomonas aeruginosa biofilms with time and carbon source

Abstract: Bacteria in nature grow mostly as biofilms, surface-associated cells enveloped by hydrated extracellular polymeric substances (EPS) of bacterial origin. The composite of EPS and biofilm cells is measured when quantifying bacterial biomass from natural samples. However, little is known regarding the relative magnitude of the EPS and cellular fractions of biofilm biomass, particularly in unsaturated systems such as soil and food surfaces. In this study, we examined the cellular and extracellular fractions of Pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…In addition, their functional roles in the EPS layer can differ. 21 Thus, as for the dimethyl methylene blue method, the application of the WGA assay depends on the presence of PNAG in mature biofilms of the bacterial strains and the interpretation of the data should also take into account the importance of the PNAG component in the matrix. Subsequently, with these three assays, a typical susceptibility study involving three model compounds: penicillin and ciprofloxacin as active antibiotics and the weak antibiotic substance rosmarinic acid as negative control was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, their functional roles in the EPS layer can differ. 21 Thus, as for the dimethyl methylene blue method, the application of the WGA assay depends on the presence of PNAG in mature biofilms of the bacterial strains and the interpretation of the data should also take into account the importance of the PNAG component in the matrix. Subsequently, with these three assays, a typical susceptibility study involving three model compounds: penicillin and ciprofloxacin as active antibiotics and the weak antibiotic substance rosmarinic acid as negative control was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…As biofilms of P. aeruginosa contain large quantities of eDNA (26)(27)(28)(29)(30) and the tfp of P. aeruginosa have been shown to bind DNA (31), we explored the possibility that eDNA may also contribute to the twitching motility-mediated biofilm expansion. We have found that incorporation of the eDNA degrading enzyme DNaseI into the nutrient media significantly decreased twitching-mediated expansion of P. aeruginosa colony biofilms by 76% (SI Results, Fig.…”
Section: Quantitative Analysis Of Cell Movements During Interstitial mentioning
confidence: 99%
“…Continuous cultivation of the strain PS88 under aerobic condition in the dark led to a high production of exocellular RNA which attained a concentration of 460 mg / L of the medium [52]. Production of extracellular DNA (eDNA) as a component of EPS has been proved to be essential for saturated biofi lm stability during the early stages of biofi lm growth [53].while, the unsaturated biofi lm of Pseudomonas aeruginosa, Pseudomonas putida, Rhodococcus erythropolis and Vivrio paradoxus contained eDNA along with polysaccharides and protein when grown as either single-or dual-species [54,55]. Epifl uorescence and electron microscopy revealed a stable fi lamentous network of eDNA closely bound to the cell surface of environmental bacterial isolates indicating a new function of extracellular DNA, possibly as a structural component.…”
Section: Compositional Analysismentioning
confidence: 99%